COMPARISON OF COLLOID (POLYGELINE) OVER CRYSTALLOID (LACTATED RINGER) PRELOADING IN PREVENTING HYPOTENSION IN PATIENTS UNDERGOING CAESAREAN-SECTION UNDER SPINAL ANAESTHESIA: Hypotension in Patients Undergoing Spinal Anaesthesia - Sohail, Major Behzad; Baig, Bilal; Boota, Muhammad; Noor, Abdullah; Haq, Imran-ul (Pakistan Armed Forces Medical Journal, 2012)
Objective: To assess efficacy of colloid (Polygeline) over crystalloid (Lactated Ringer) preloading in preventing hypotension in patients undergoing caesarean-section under spinal anaesthesia. Study design: Randomized control trial. Settings: The study was conducted in department of Anesthesiology and Intensive care Combined Military Hospital Peshawar over a period of 6 months from 01 March 2007 to 31 August 2007. Material and Methods: One hundred patients fulfilling the inclusion criteria were selected for study and divided into two groups of 50 each. Group A was given 500 ml Polygeline as preloading solution while group B received 1 liter of Ringer’s Lactate as preloading solution just before administration of spinal anaesthesia. Heart rate and systolic blood pressure were recorded at 01 min, 05 mins, 10 mins, 15 mins, 20 mins, 30 mins and 45 mins after the performance of spinal block. Dose of ephedrine given to treat hypotension after the block was also recorded. Results: There was significant difference in terms of heart rate and systolic arterial pressure 1 and 5 minutes after block between both the groups. There was also significant difference in terms of dose of ephedrine between both the groups. Conclusion: Polygeline is more effective than Ringer’s Lactate as preloading fluid in preventing hypotension for caesarean section under spinal anaesthesia.